SEMINAR RESEARCH AND THE RELATION WITH DIFFERENT STRATEGIES AND METHODOLOGIES OF LEARNING AND TEACHING - Ospina Rave, Beatriz Elena; Aristizábal Botero, Carlos Andrés (Investigación y Educación en Enfermería, 2009)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Objective: this Article shows the way how it develops a seminar of research and the relations with different strategies and methodologies of learning and teaching used in the seminar. Methodologie: the reasearch was made during 2004-2005 in two seminars of reasearch in the Nursing Faculty of the University of Antioquia. It used an the focalizad type of the etnographic methodologie, emphazasing the observation in the groups of students and the two professors that coordinated the seminars. The information was gathered using three strategies: Revision of documental sources, in depth interviews with students and professors, observation. Results: it was found that the seminar its desingned starting from a formal structure, where the profesor organize the contents according to the needs that he assume the environment has concerning to the reaserch and how he expect the student face the situation. Conclusions: the research seminar it´s designed and Developer from a procedural structure that privilege the contents that comes from the methods and the technic of research. The way how the participants of the process of learning and teaching interact makes stronger the procedural character of this.